Modelo de Distribución Geográfica de la Especie Leopardus tigrinus (VU) Bajo Escenarios de Cambio Climático en Colombia (2023)
Among the species of mammals in danger of extinction and classified in a vulnerable state (VU), both by the International Union for Conservation of Nature (IUCN), as well as by resolution 1912 of 2017 of the Ministry of Environment and Sustainable Development (MADS) finds Leopardus tigrinus (MADS, 2017), or commonly known as "Ocilla" or "Woolly Tigrillo", the current status of the species has been affected by various factors, among them, the pressure exerted by human activities such as deforestation, habitat loss and the hunting, in Colombia the species is found mainly in the Andes Mountains and has the record of being the smallest feline that inhabits the country, its distribution is throughout the entire continent American, from northern Argentina to Costa Rica (Arias, 2016).